2001
DOI: 10.1021/ja017198n
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Intramolecular Aminopalladation:  Enantioselective Synthesis of Vinyl-Substituted 2-Oxazolidinones, 2-Imidazolidinones, and 2-Pyrrolidinones

Abstract: A new catalytic asymmetric synthesis of five-membered nitrogen heterocycles is reported. This synthesis employs ferrocenyloxazoline palladacycles (FOP trifluoroacetate catalysts) 2 and 4 and proceeds by a catalytic cycle involving Pd(II) intermediates. For example, prochiral (Z)-4-acetoxy-2-buten-1-ols are condensed with an arylsulfonyl isocyanate and the derived allylic N-arylsulfonylcarbamates cyclize in situ upon addition of 0.5-5 mol % of 2 or 4 to form 4-vinyloxazolidin-2-ones 6, 13, and 15 in high yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(63 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…Recently, a number of C * -chiral enantiopure exo [48][49][50], endo [48,[50][51][52][53][54][55][56][57][58][59][60][61][62] and pincer-type [58,[63][64][65][66][67][68][69][70] cyclopalladated oxazolines with a five-membered metalacycle have been reported (Chart 2). Other cyclopalladated oxazolines with planar and central chirality have also been studied [38,[71][72][73][74][75][76][77][78][79][80]. It has also been shown that the formation of five-membered oxazolinederived metalacycles complies with the endo rule: the preference of endo palladation over exo [48,50].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of C * -chiral enantiopure exo [48][49][50], endo [48,[50][51][52][53][54][55][56][57][58][59][60][61][62] and pincer-type [58,[63][64][65][66][67][68][69][70] cyclopalladated oxazolines with a five-membered metalacycle have been reported (Chart 2). Other cyclopalladated oxazolines with planar and central chirality have also been studied [38,[71][72][73][74][75][76][77][78][79][80]. It has also been shown that the formation of five-membered oxazolinederived metalacycles complies with the endo rule: the preference of endo palladation over exo [48,50].…”
Section: Introductionmentioning
confidence: 99%
“…The most common palladacycles are derived from organic molecules containing N-donor groups such as tertiary amines and imines with a five or six-membered chelate. Among them, cyclopalladated ferrocene derivatives are particularly interesting since planar chirality may be introduced in the 1,2-disubstituted ferrocene moiety which shows great potential in asymmetric synthesis and catalysis [5,6]. In this respect, we have reported a variety of achiral and chiral cyclopalladated complexes having Schiff base type of ferrocenylimine ligands [7][8][9][10][11] and found that some cyclopalladated complexes are efficient catalysts for the Heck [9] and Suzuki reactions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Palladacycles have attracted much attention in the homogeneous catalysis of reactions such as cross-coupling, [21] allylic amination, [22] allylic rearrangement [23] and so on. We have previously explored the use of palladacycles for the asymmetric Claisen rearrangement reaction [24] and also investigated their potential in C À N bond formation scenarios such as hydroamination.…”
mentioning
confidence: 99%